Contextualization: A Theology of Gospel and Culture, karya: Nicholls, Bruce J. - Martin Susanto (Jurnal Teologi Amreta (ISSN: 2599-3100))
Contextualization: A Theology of Gospel and Culture, karya: Nicholls, Bruce J.